OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY FEATURES OF ANGIOID STREAKS. Issue 11 (November 2018) - Corbelli, Eleonora; Carnevali, Adriano; Marchese, Alessandro; Cicinelli, Maria Vittoria; Querques, Lea; Sacconi, Riccardo; Bandello, Francesco; Querques, Giuseppe
Abstract : Purpose: To analyze the optical coherence tomography angiography features of eyes affected with angioid streaks (AS) and to evaluate their ability to predict choroidal neovascularization (CNV) activity. Methods: Angioid streaks were individuated from a pool of consecutive patients. Eyes with and without CNV were evaluated by multimodal imaging. Results: Thirty-eight eyes of 19 consecutive patients diagnosed with AS were included. Thirty of 38 eyes with CNV and 8 of 38 eyes without CNV were included. In the majority of cases, CNV showed on optical coherence tomography angiography tangled appearance always associated with signs of neovascular inactivity on multimodal imaging (100%–0%, inactive-active, respectively). Choroidal neovascularization cases showing interlacing appearance were often associated with signs of neovascular activity on multimodal imaging (71.4%–28.6%, active-inactive, respectively). Optical coherence tomography angiography revealed a total of 27 AS, of which 20 appeared as a choriocapillary rarefaction, and in 7 AS, optical coherence tomography angiography choriocapillary segmentation revealed an irregular vascular network, possibly representing fibrovascular tissue over the crack-like breaks in Bruch membrane. Conclusion: Optical coherence tomography angiography is a noninvasive tool to detect the presence of CNV secondary to AS and to evaluate CNV activity. Optical coherence tomography angiography is able to add a novel element to the multimodal imaging characterization of AS. Abstract : The aim of this study was to analyze retrospectively optical coherence tomography angiography features of eyes affected by angioid streaks with and without choroidal neovascularization and to propose a new classification criterion.